Role of endothelins in trinitrobenzene sulfonic acid-induced colitis in rats - YEGEN, BERRAK; GÜLLÜOĞLU, MAHMUT BAHADIR; YEGEN, ŞEVKET CUMHUR (KARGER, 1999)
To determine the role of endothelins (ET) on experimental colitis, following intracolonic trinitrobenzene sulfonic acid administration, rats were given orally either bosentan (BS), a nonselective ET receptor antagonist (100 mg/kg in 5% arabic gum), or arabic gum by gavage for 2 or 14 days. Macroscopic damage scores obtained in the vehicle (1.4 +/- 0.4), acute (4.8 +/- 0.6) and chronic (3.8 +/- 0.3) colitis groups were significantly higher than in the control group (0). BS treatment reduced the scores in both acute (3 +/- 0.5) and chronic (2.3 +/- 0.5) colitis groups. Myeloperoxidase (MPO) activities of colonic tissues were elevated in acute and chronic colitis groups (325.1 +/- 44.9 and 431.8 +/- 54.6 U/g wet weight) as compared with the control group (73.6 +/- 11 U/g wet weight). Plasma protein oxidation levels were found to be significantly increased in the chronic colitis group (1,158.1 +/- 63.4 nmol/ml) compared with the control, ethanol and acute colitis groups (274.3 +/- 23.1, 490 +/- 52.2 and 422.2 +/- 50.5 nmol/ml). BS treatment significantly reduced both the protein oxidation level (375.5 +/- 46.9 nmol/ml) and MPO activity (167.5 +/- 35.8 U/g wet weight). The results of the present study suggest the involvement of ETs in the pathogenesis of colonic injury in this animal model of colitis.
Keywords: experimental colitis; bosentan; endothelins; colonic motility; myeloperoxidase activity; carbonyl content; INFLAMMATORY BOWEL-DISEASE; COLONIC INFLAMMATION; RECEPTOR ANTAGONIST; ULCERATIVE-COLITIS; MODEL; PEPTIDE; CELLS; CLONING; INJURY; IMMUNOREACTIVITY